EXTRACURRICULAR SPORTS AS A TOOL FOR CHARACTER DEVELOPMENT AND WELL-BEING IN SECONDARY SCHOOL STUDENT: SCOPING REVIEW - Trisnar Adi Prabowo; Asyidika Vito Indarto; Febriansyah Dwi Cahyo; Mar'atul Afifah; Ahmad Zakaria (Riyadhoh : Jurnal Pendidikan Olahraga, 2025)
The purpose of this study is to provide broad and in-depth information on how extracurricular sports can be utilized for character development and student welfare in secondary schools. This research method uses scoping review, and literature search using databases such as PubMed, Scopus, Web of Science, Google Scholar with predetermined keywords. The inclusion criteria were articles written 1) in English, 2) have open access, 3) the sample is students in secondary school, 4) the article publication is 2020 - 2024 which focuses on extracurricular sports programs and their impact on students. The results of this study successfully analyzed 7 scientific articles with an average sample age of 12 - 18 years, which had been systematically selected. Extracurricular sports have great potential to improve students' character and well-being. Analysis of various interventions in the seven studies reviewed showed a diversity of approaches, ranging from passive observation of student participation to the implementation of structured sports programs such as step aerobics programs or Olympic education programs. Despite the variation in interventions, findings consistently highlight the importance of comprehensive support from schools, including adequate resource allocation, ongoing teacher training, and inclusive and diverse program design. Ongoing evaluation and monitoring are also crucial to ensure program effectiveness and make necessary adjustments. Although findings consistently emphasize the importance of ongoing support and evaluation, methodological limitations and literature coverage limit the generalizability of the findings. Further research is needed to confirm the results and provide a more comprehensive understanding.